TRANSFORMASI GAYA KEPEMIMPINAN MENUJU ERA DIGITAL: ANALISIS KEPEMIMPINAN SUPPORTIVE DAN AUTHENTIC DALAM ORGANISASI PENDIDIKAN - Prianti, Nila; Darlina, Nella; Gistituati, Nurhizrah; Rusdinal, Rusdinal; Nellitawati, Nellitawati (Jurnal Kepemimpinan dan Pengurusan Sekolah, 2025)
Digital transformation has changed the landscape of educational organisations—replacing many face-to-face interactions with hybrid and virtual interactions and requiring education leaders to adapt their leadership styles. This article reviews the 2015–2025 literature on two leadership styles relevant to the digital age: supportive leadership and authentic leadership, and how these two styles help build trust and team support in the digital education environment. The research method was a systematic literature review of relevant journals, scientific articles, policy reports, and literature reviews. The synthesis results show: (1) effective digital leadership requires a combination of personal support and openness/authenticity to maintain trust; (2) concrete practices include structured communication, technology support policies, collaborative learning, and decision transparency; (3) the main obstacles are uneven digital literacy, cultural resistance, and infrastructure limitations. Recommendations are provided for school leaders and educational institutions to implement interventions focused on strengthening interpersonal relationships, establishing clear virtual work rules, and improving staff digital capabilities.